Moderating the Work System in the Transformation of Industrial Relations and Performance Management: A Study of Hospitality Tourism Human Resource Development - Liana, Tri Melda Mei; Soekatendel, Eddy; Dalimunthe, Ritha F.; Lumbanraja, Prihatin (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to understand the moderating role of the work system in the transformation of industrial relations and performance management in the context of human resource development (HRD) in hospitality tourism in North Sumatra. The research method used is a qualitative approach by extracting data from various sources, such as interviews, observations, and documentation studies. However, this research also shows that there are still challenges in the development of hospitality tourism human resources in North Sumatra. Some of the challenges identified include a lack of understanding of the importance of a good work system, lack of worker involvement in decision-making, and ineffective communication between management and workers. Therefore, sustained efforts are needed in improving good work systems, as well as worker empowerment in decision-making and effective communication in an effort to improve performance management in North Sumatra's hospitality tourism sector. The conclusion of this brief provides an overview of the complexity of interactions between the factors of performance management, industrial relations, work systems and human resource development in the context of the hospitality industry in North Sumatra. This can serve as a basis for stakeholders to improve performance management, work systems and human resource development in the hospitality tourism sector in the region.